KOORDINASI KERJA FOOD AND BEVERAGE SERVICE DENGAN FOOD AND BEVERAGE PRODUCT DALAM OPERASIONAL BREAKFAST DI HOTEL ASTON TANJUNGPINANG - Kurisnawan Nuralam; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The cooperation between the two sections in a department so common we meet, work coordination that exists between the restaurant and the kitchen is one form of cooperation.In this study, researchers using qualitative methods is as prosuder for processing data obtained from observations and interviews, to find out the cause of the increasing number of guest complaints in 2016.The conclusion from the data processing results show that, the coordination that occurs between the food and beverage service to the food and beverage product goes well, seeing the results of interviews with the employees of food and beverage service that states coordinate their work better and compact as a team.Keywords: Coordination of work, food and beverage service, food and beverage products, operational breakfast.